Brazilian Portuguese version of the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) Axis I: Cross-cultural adaptation, criterion validity, and reliability - Antunes da Cunha, Taísi; Alstergren, Per; Pereira Júnior, Francisco José; Gonçalves, Daniela Aparecida de Godoi [UNESP]; Chaves, Thaís Cristina; Biasotto-Gonzalez, Daniela Aparecida (Elsevier, 2025)
Background: The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) is a biaxial instrument used worldwide for TMD assessment. Objective: To translate, cross-culturally adapt, and assess the criterion validity and reliability of the Brazilian Portuguese version of the DC/TMD Axis I. Methods: The translation and cross-cultural adaptation of Axis I into Brazilian Portuguese followed the recommendations of the International Network for Orofacial Pain and Related Disorders Methodology. For the formal assessment, 117 Brazilians with TMD completed the translated version of the TMD Pain Screener, the Symptom Questionnaire, and the Numeric Pain Rating Scale for orofacial pain intensity assessment. Subsequently, a standardized clinical examination was performed. Fifty-one participants were examined by two raters for interrater reliability, and 53 participated on a second assessment day for intrarater reliability analyses. TMD Pain Screener criterion validity was assessed through sensitivity, specificity, and ROC curve. Kappa and intraclass correlation coefficient (ICC) were used to analyze reliability for categorical and continuous data, respectively. Results: The translated version achieved language equivalency. High accuracy was found for the Brazilian Portuguese version of the TMD Pain Screener short form (AUC = 0.95) compared to the long form, as well as high intrarater reliability (ICC 0.88). Moderate to almost perfect reliability was found for painful TMD diagnoses and disc displacement with reduction. Conclusions: The Brazilian Portuguese version of the DC/TMD Axis I is valid and reliable for screening painful TMD and for painful DC/TMD diagnoses.
Keywords: Brazil; orofacial pain; Reliability; Temporomandibular disorder; Translations; validity